2004
DOI: 10.1002/bem.20071
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low frequency magnetic fields originating from equipment used for assisted reproduction, umbilical cord and peripheral blood stem cell transplantation, transfusion, and hemodialysis

Abstract: The extremely low-frequency (ELF) magnetic fields (MFs) originating from equipment used for assisted reproduction, umbilical cord-blood and peripheral-blood stem cell transplantation, transfusion, and hemodialysis were measured. The ELF-MF values were 0.1-1.2 microT on clean benches, <0.1-8.0 microT on inverted microscopes, <0.1-13.6 mmicroT in CO2 incubators, 4.3-11.5 microT in centrifuges, 0.4-18.8 microT in programmed freezers, <0.1-0.3 microT in deep freezers, 0.3-3.1 microT on cell separators, and 0.2-0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This is an expected outcome since 60 Hz is the frequency of the power supplied to all the incubators. Similarly, 50 Hz can be observed in the incubators fed with electrical power supplied at that frequency [Moriyama et al, 2005;Hansson Mild et al, 2009]. Because of this, all the data presented in this report for TVMF analysis are only the 60 Hz amplitudes.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…This is an expected outcome since 60 Hz is the frequency of the power supplied to all the incubators. Similarly, 50 Hz can be observed in the incubators fed with electrical power supplied at that frequency [Moriyama et al, 2005;Hansson Mild et al, 2009]. Because of this, all the data presented in this report for TVMF analysis are only the 60 Hz amplitudes.…”
Section: Resultsmentioning
confidence: 68%
“…Previous studies have suggested this to be a problem by giving a glimpse at the TVMF present in biological incubators [Hansson Mild et al, 2003Moriyama et al, 2005]. Such factors are usually outside the awareness or control of the researcher.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, other occupational environments have been investigated [McCurdy et al, 2001;Deadman and Infant-Rivard, 2002;Forssén et al, 2004;Szabó et al, 2006;Mee et al, 2009]. A few studies have described ELF fields emitted by systems used for therapy or diagnosis in hospitals [Paul et al, 1994;Bullough et al, 1996;Li et al, 2000;Lee et al, 2003;Riminesi et al, 2004;Moriyama et al, 2005;Bradley et al, 2007;Roh et al, 2009]. Although the data indicate that medical personnel working in hospitals is a group potentially exposed to relatively strong ELF MF, the information on the characteristics and levels of exposure in specific job categories in hospitals is still scarce and incomplete.…”
Section: Introductionmentioning
confidence: 94%
“…Each lamp was controlled by a pair of three-way switches that were installed at SW1' and SW2' in the studied room, and SW1 and SW2 in the room downstairs. We used a Triaxial ELF Magnetic Meter Model 4090 (Bell Technology, Orlando, FL, USA) to measure the ELF-MF magnitudes (|B|) at floor level and at heights of 0.50, 1.00, 1.50, 2.00, and 2.50 m [Gauger, 1985;Moriyama et al, 2005].…”
mentioning
confidence: 99%